Sources of Productivity Growth in Uganda : The Role of Interindustry and Intra-industry Misallocation in the 2000s - Dennis, Allen; Mengistae, Taye; Yoshino, Yutaka; Zeufack, Albert (World Bank, Washington, DC, 2017)
Uganda's growth in gross domestic product of the 2000s was accompanied by high growth rates of labor productivity across industries producing tradable goods and services. This came about primarily as a result of investment in equipment and other fixed assets, but also entailed substantial gains in total factor productivity Based on data from two waves of the Uganda Business Indicators survey this paper estimates that economy wide aggregate labor productivity and aggregate TFP grew at average annual rates of 13 t and 3 percent, respectively between survey years 2002 and 2009. Part of the growth in productivity on each measure reflected gains from technical progress made at the establishment level and within narrowly defined industries. But it was also in part the outcome of reallocation of labor and capital within as well as across industries. In particular, the paper estimates that about one-fifth of the aggregate growth in labor productivity between the two years reflected the shifting of labor toward industries and sectors where it was more productive on average and at the margin. The rest of the observed growth in labor productivity reflected gains made within narrowly defined industries. But almost in every case 55 to 90 percent of the observed "within industry" growth in labor productivity represented allocative efficiency gains from the correction of intra-industry inter-firm misallocation of labor. The balance of the observed within-industry growth in labor productivity represented establishment-level gains in technical efficiency.